2005
DOI: 10.1097/01.gim.0000162877.87333.9a
|View full text |Cite
|
Sign up to set email alerts
|

Deficient knowledge of genetics relevant for daily practice among medical students nearing graduation

Abstract: Purpose: The objective of this study was to investigate whether the knowledge of genetics relevant for daily practice among medical students nearing graduation in the Netherlands was sufficient to react appropriately to the change of relevance of genetics in medicine. Methods: A computer examination validated in a group of clinical geneticists, medical students nearing graduation, and nonmedical students. The examination consisted of 215 genetic questions classified by the designers into three categories of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 15 publications
1
40
0
2
Order By: Relevance
“…The lack of adequate health care professional education and the lack of patient education are just two of the potential barriers to the adoption of pharmacogenetic testing (Baars et al 2005;Newman and Payne 2008). This was also one of the key conclusions of a recent European Commission Joint Research Centre Report on pharmacogenetics and pharmacogenomics (Zika et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of adequate health care professional education and the lack of patient education are just two of the potential barriers to the adoption of pharmacogenetic testing (Baars et al 2005;Newman and Payne 2008). This was also one of the key conclusions of a recent European Commission Joint Research Centre Report on pharmacogenetics and pharmacogenomics (Zika et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, at present, most doctors do not feel that they have the responsibility, time or capacity to provide and interpret genetic tests (Fargher et al 2007). Clearly, inadequate education both at undergraduate and postgraduate levels is a potential barrier to the widespread uptake of pharmacogenetic tests (Baars et al 2005;Newman and Payne 2008). In 2005, the International Society of Pharmacogenomics (ISP), recognizing this unmet need, published a number of recommendations, including one for undergraduate medical teaching of pharmacogenetics (Gurwitz et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…16 A research project among medical students nearing graduation recently showed that the students lacked the appropriate knowledge of genetics that is relevant for daily practice, and that changes in the basic medical curriculum should be made as well. 27 Furthermore, as demonstrated by Challen et al 28 the integration and visibility of genetics in the medical curricula in several countries in Europe was very limited.…”
Section: Deficiency Of Genetic Knowledge and Its Impactmentioning
confidence: 99%
“…As larger volumes of personal genetic information are produced, it will be important to examine the criteria that patients and clinicians use to assess the value of results from genomic testing. 34 In combination with the limited familiarity that many physicians have with clinical genetic testing, 35,36 these considerations highlight some of the many data-management challenges that will be associated with clinical applications of WGS. Similar to WGS, multiplexed forms of genetic risk assessment present many of these same challenges.…”
Section: Disclosing Results and Preparing For Lifelong Follow-upmentioning
confidence: 99%